The growth paths of state-society relations : power dynamics, industrial policy, and the pursuit of inclusive and sustainable growth - Sabry, Mohamed Ismail (Emerald Publishing Limited, 2023)
Institutions shape states, society, businesses, and the interactions between them. Understanding how these interactions shape the growth paths of different countries is crucial to monitoring policy outcomes and gauging creditable impact. The Growth Paths of State-Society Relations highlights how different state-society relations have developed, the power relationships that characterize their different forms or modes, and the wider growth paths that are likely to emerge as a result. Combining case studies with empirical and theoretical game analysis, Mohamed Ismail Sabry presents four State-Business-Labor Relations (SBLR) modes for considering the power relationships at play in these interactions. Analyzing four significant case studies featuring Germany, the USA, China, and Russia, Sabry investigates the emergence of these various modes, particularly whether they arise out of institutional settings or special socioeconomic or historical circumstances. Considering variables such as levels of productivity, long-run economic growth, inequality, and sustainability, chapters also discuss how the SBLR modes affect the growth paths of each example country, particularly through policies related to Technology and Industry 4.0, Green transformation, and social welfare. Providing a rationale for institutional change as well as suggestions for power restructuring within a state-society relationship, The Growth Paths of State-Society Relations offers a unique and nuanced analysis of the perpetual interplay between government, business, and society.
Keywords: Sustainable development.; Social systems.; Industrial policy.; Business & Economics -- Development -- Sustainable Development.; Development economics & emerging economies.; elektronické knihy; electronic books